Kinetics of IL-6, C-reactive Protein and Fibrinogen Levels in COVID-19 Outpatients Who Evolved to Hypoxemia - Sérgio Paulo de Mello Mendes-Filho; Rebeca de Souza Pinheiro; Fernanda Simão Martins; Paulo Jose Giroldi; Raul Honorato e Melo; Edcleia Lopes de Oliveira; Anibal Borin dos Santos; Dayse Cristina Oliveira Medeiros; Jéssica Amaral Lopes; Yury Oliveira Chaves; Juliana Pavan Zuliani; Paulo Afonso Nogueira (SAGE Publishing, 2024)
Introduction: Despite the efficacy of the COVID-19, the search for improvements in the management of severe/critical cases continues to be important. The aim is to demonstrate the kinetics of 4 serological markers in patients with COVID-19 who evolved in hypoxemia. Methods: From June to December 2020, the Health Secretariat of Rondônia State, Brazil, established a home medical care service team (HMCS) that provided clinical follow-up for health professionals and military personnel with COVID-19. The clinical and laboratory monitoring was individualized at home by a nursing and medical team. In addition to laboratory parameters, C-reactive protein (CRP), interleukin-6 (IL-6), fibrinogen, and D-dimer levels were periodically taken to monitor the evolution of treatment. Results: Of 218 patients telemonitored, 48 patients needed special care by the HMCS team due to shortness of breath. Chest tomography showed multiple ground-glass shadows and lung parenchymal condensations that was compatible with secondary bacterial infection associated with leukocytosis, for which antibiotics were prescribed. The symptoms were accompanied by increases of CRP and IL-6 levels followed by fibrinogen after a few days, for which an anticoagulant therapy was included. Thirty-three patients evolved to improvements in clinical signs and laboratory results. Between the sixth and eighth day of illness, 15 patients presented signs of hypoxemia with low O 2 saturation accompanied with an increase in the respiratory rate, with some of them requiring oxygen therapy. As they did not present signs of clinical severity, but their laboratory markers showed an abrupt IL-6 peak that was higher than the increase in CRP and a new alteration in fibrinogen levels, they received a supplemental dose of anticoagulant and a high dose of corticosteroids, which resulted in clinical improvement. Conclusion: Our study demonstrates that monitoring of IL-6 and CRP may identify precocious hypoxemia in COVID-19 patients and prevented the progressive deterioration of the lung injury.